2018
DOI: 10.3390/microorganisms6040119
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Efficiency of Molecular Markers for the Species Identification of Gregarines Isolated from the Mealworm and Super Worm Midgut

Abstract: Protozoa, of the taxon Gregarinasina, are a heterogeneous group of Apicomplexa that includes ~1600 species. They are parasites of a large variety of both marine and terrestrial invertebrates, mainly annelids, arthropods and mollusks. Unlike coccidians and heamosporidians, gregarines have not proven to have a negative effect on human welfare; thus, they have been poorly investigated. This study focuses on the molecular identification and phylogeny of the gregarine species found in the midgut of two insect speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
3
1
0
Order By: Relevance
“…The 1.5% genetic distance between the two sequences is in agreement with previously described inter-specific levels of genetic divergence that, for example, distinguish Gregarina niphandrodes from Gregarina polymorpha (1.44%) [31]. However, it should be noted that, according to the same authors, such "low" genetic divergence could also correspond to "intra-specific" variability [31]. Certainly, additional studies will be needed to clarify this issue, but we recently demonstrated that two marine gregarines with an almost identical SSU rDNA sequence (1 bp difference for 1702 positions, i.e.~0.05% divergence) displayed~10% overall nucleic acid divergence at the genomic level, preventing genetic crossing, i.e.…”
Section: Molecular Data Support Distinct Speciessupporting
confidence: 90%
See 2 more Smart Citations
“…The 1.5% genetic distance between the two sequences is in agreement with previously described inter-specific levels of genetic divergence that, for example, distinguish Gregarina niphandrodes from Gregarina polymorpha (1.44%) [31]. However, it should be noted that, according to the same authors, such "low" genetic divergence could also correspond to "intra-specific" variability [31]. Certainly, additional studies will be needed to clarify this issue, but we recently demonstrated that two marine gregarines with an almost identical SSU rDNA sequence (1 bp difference for 1702 positions, i.e.~0.05% divergence) displayed~10% overall nucleic acid divergence at the genomic level, preventing genetic crossing, i.e.…”
Section: Molecular Data Support Distinct Speciessupporting
confidence: 90%
“…Overall, 22 different bases were identified in this 1638 bp region that could be used to delimit the species. The 1.5% genetic distance between the two sequences is in agreement with previously described inter-specific levels of genetic divergence that, for example, distinguish Gregarina niphandrodes from Gregarina polymorpha (1.44%) [31]. However, it should be noted that, according to the same authors, such "low" genetic divergence could also correspond to "intra-specific" variability [31].…”
Section: Molecular Data Support Distinct Speciessupporting
confidence: 89%
See 1 more Smart Citation
“…These protozoan parasites may also good materials for studies on parasite-host coevolution and biological control of insects 3 , 4 . However, the gregarines have only been poorly explored compared to those much better studied vertebrate pathogens 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%